2012
DOI: 10.1039/c2em30026e
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the potential of Ipomoea nil ‘Scarlet O'Hara’ for ozone biomonitoring in the sub-tropics

Abstract: This study aimed to analyze critically the potential of Ipomoea nil'Scarlet O'Hara' for O(3) biomonitoring in the sub-tropics. Four field experiments (one in each season of 2006) were carried out in a location of the city of São Paulo mainly polluted by O(3). Each experiment started with 50 plants, and lasted 28 days. Sub-lots of five plants were taken at intervals between three or four days long. Groups of four plants were also exposed in closed chambers to filtered air or to 40, 50 or 80 ppb of O(3) for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The appearance of visible injury is a common symptom observed in vine species exposed to O 3 . It was registered for example by Saitanis (2003) in Vitis vinifera in Greece, by Manning and Godzik (2004) in Humulus lupulus in Central and Eastern Europe and by Ferreira et al (2012) in Ipomoea nil 'Scarlet O'Hara' in the state of São Paulo, Brazil. The confocal analyses indicated a degradation of chlorophylls inside the chloroplasts of chlorotic leaves under elevated ozone levels, compared to chlorophyll emissions in asymptomatic leaves of plants exposed to ambient ozone level.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of visible injury is a common symptom observed in vine species exposed to O 3 . It was registered for example by Saitanis (2003) in Vitis vinifera in Greece, by Manning and Godzik (2004) in Humulus lupulus in Central and Eastern Europe and by Ferreira et al (2012) in Ipomoea nil 'Scarlet O'Hara' in the state of São Paulo, Brazil. The confocal analyses indicated a degradation of chlorophylls inside the chloroplasts of chlorotic leaves under elevated ozone levels, compared to chlorophyll emissions in asymptomatic leaves of plants exposed to ambient ozone level.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Japanese morning glory (Fig. S1.7) has been proposed as a possible bio-indicator for tropical areas (Ferreira et al, 2012;Moraes et al, 2014), and the black locust (Robinia pseudoacacia, Fig. 3.5) is a well-known ozone bio-indicator in the USA (Innes et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In general, trees have a high potential to mitigate the effects of atmospheric pollution (Martins et al, 2021;Ramon et al, 2023). Biomonitoring studies of air quality with plants have identified contamination hotspots in places with high environmental impact, thus denoting key points in the urban area that can be afforested (Ferreira et al, 2012;Ferreira et al, 2017a;Ferreira et al, 2017b;Zabotto et al, 2020;Theophilo et al, 2021).…”
Section: Socio-environmental Indicators Of Gbbr Municipalitiesmentioning
confidence: 99%